(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
In line of the huge scope of the digital context, the number of subscribers of digital services, and the number of digital devices, levels of energy intake have reached alarming levels during the last decade. By 2020, the number of linked devices will have augmented almost to forty nine billion, and in the coming years almost by 2030, it will have increased to 100 billion. As a result, experts anticipate a massive increase in content size and data usage rate (hundreds of thousand times larger in coming decade than it was in past two decades) at the cost of extreme carbon emissions into the atmosphere. As the Internet of Things (IoT) connects everything in the smart world, energy usage is an issue and a promising study field. A green IoT is proposed in order to achieve a low power consumption IoT. The purpose of this article is to offer an overview of green IoT. It also goes through the green IoT life cycle, which includes green design, green manufacture, green use, and green recycling. Green IoT technologies are also explored, such as green tags, green sensor networks, and green internet technologies. In addition, there are studies on IoT using fifth gen technologies and IoT for smart metropolises. Finally, future research topics as well as outstanding issues in the field of green IoT are discussed.